Effect of body condition score on biochemical parameters and hormonal profiles during the mating period in Ouled Djellal ewes in arid zone - Titaouine, M; Mezerdi, F; Makhlouf, A; Mohamdi, N; Mohamdi, H (Journal of the Hellenic Veterinary Medical Society, 2023)
ABSTRACT This study aims to evaluate the effect of body condition score (BCS) on hormonal profiles and to reveal their influence on the blood metabolites in Ouled Djellal ewes during the mating period. The experiment was conducted on thirty, clinically healthy and non-pregnant, Ouled Djellal ewes which have been kept into two groups according to their body condition score (Group I: BCS < 2.50 units; n = 13, Group II: BCS > 2.50 units; n = 17). In both groups, oestrus was synchronized using hormonal patterns then the ewes were left to be naturally inseminated. Blood samples were collected at the time of the sponge removal. Plasma concentrations of glucose, triglycerides, cholesterol, total protein, albumin, creatinine, urea, triiodothyronine, thyroxine and Progesterone were recorded. The plasma level of triglycerides and thyroid hormones (T3 and T4) increase significantly (P < 0.01) in group II. Progesterone concentrations were similar (P ≥ 0.05) in both groups at mating period, although we recorded higher rate in group I. Therefore, we conclude that body condition score has a significant impact on some hormone profiles and blood parameters during the mating period.